Optimized Design of Rotor Barriers in PM-Assisted Synchronous Reluctance Machines With Taguchi Method - Maryam Naseh; Saeed Hasanzadeh; Seyed Mohammad Dehghan; Hossein Rezaei; Ameena Saad Al-Sumaiti (IEEE Access, 2022)
In recent years, PM-assisted synchronous reluctance machines simplicity, robustness, efficiency, and temperature capacity (SynRMs) make them a viable alternative in various applications. The poor power factor (PF) and high torque ripple are the main challenges of SynRMs, which necessitate robust optimization improving the mentioned demerits. However, the optimization algorithms usually rely on complex analytical models; in this paper, in order to optimize, the design of experiments with the Taguchi method has been used. Taguchi is a simple and effective optimization method and requires a small number of experiments and experience. Also, to select the best combination in multi-objective optimization, the TOPSIS method has been utilized to prioritize the optimal solutions. The proposed method is evaluated by finite element analysis (FEA).